1203 SUPPORTING SAFE SWALLOWING OF CARE HOME RESIDENTS WITH DYSPHAGIA: HOW DOES CARE COMPARE WITH GUIDANCE?. (16th January 2023) - Wilson, J; Loveday, H; Tingle, A; Griffin, H; Goerzig, A
Abstract: Introduction: Dysphagia affects up to 70% of nursing home residents, causes significant morbidity and increased hospital admissions. Speech and language therapists (SLT) make recommendations to reduce the risk of aspiration and support safe eating and drinking but have limited capacity to offer ongoing guidance to care home staff. This study aimed to measure the mealtime experience of residents with dysphagia, how this compared with SLT advice and what factors influenced care. Methods: The safety of nutrition/hydration care of residents with dysphagia in 2 care homes was observed using a structured tool capturing 12 elements of expected practice. Observed practice was compared to recommendations in SLT/care-plans. Interviews with staff aimed to understand factors that contributed to how dysphagia care was delivered. Results: SLT recommendations for 18 residents with dysphagia were predominantly focused on food/fluid modification, other safe swallowing strategies were mentioned less frequently. 66 episodes of mealtime care for 11 residents were observed. Adherence to SLT/care-plan recommendations for food texture, posture and alertness of the resident was observed on 90% of occasions, but on less than 60% of occasions for alternating food and drink, prompting resident during feeding, ensuring swallow completed and throat/mouth clear. Compliance with recommended fluid thickness was 68%; thickening was frequently not aligned to required IDDSI level. Nutrition care was less safe when residents were fed in the dining room when multiple care staff were present. Interviews with 11 care home staff found care-plans were rarely consulted, care needs were communicated verbally during handover, and training was targeted at fluid modification but not at other safer swallowing strategies. Limited knowledge about causes of coughing whilst eating/drinking drove inappropriate SLT referrals. Conclusions: A safe swallowing culture that addresses system and workforce issues in care homes would improve the experience of residents with dysphagia and reduce their risk of aspiration.